Success Factors for Improving Logistics in a Middle-Income Country - Raballand, Gaël; Arvis, Jean-François; Bellier, Michel (World Bank, Washington, DC, 2012)
This note presents the main lessons drawn from an analytical and sector work on trade logistics in Morocco. Public and private counterparts recognized the positive impact of the World Bank's report to catalyze and accelerate reforms' pace and to facilitate cooperation between public and private parties involved in logistics reforms. A careful preparation process and a strong buy-in from public and private stakeholders involved in logistics in Morocco made this Economic Sector Work (ESW) successful. To achieve this outcome, the Bank team based efforts on a tailored approach to commission background studies, knowledge dissemination during preparatory work and a detailed action plan in order to create a rapid and positive impact on improving logistics. The Moroccan example also demonstrates that, in a middle-income country, detailed and relevant action plan under a strong political willingness and commitment to reform can achieve rapid and significant results.